PERAN YAYASAN DALAM ARAS KEWENANGAN UNTUK MEWUJUDKAN TATA KELOLA PERGURUAN TINGGI SWASTA YANG BAIK (GOOD UNIVERSITY GOVERNANCE) - Azan Elwan (LPPM STISIP IMAM BONJOL, 2022)
Foundations and Private Universities become an organizational unit that has the same activities and objectives in terms of the implementation and management of Higher Education in accordance with the laws and regulations to be managed based on good university governance in accordance with the established management autonomy. The purpose of this study is to empirically examine the role of foundations and find a best practice on the management autonomy authority to realize good university governance. This research is a descriptive study with a quantitative approach with a survey method through questionnaires to 21 respondents from foundation leaders, leaders of private universities, lecturers of structural officials at private universities in Padang City. The data analysis technique uses SEM which is operated through SmartPLS 3.0 software. The results of this study indicate that there is a significant positive influence of good university governance and significant management autonomy on the role of foundations in the level of authority to realize good governance of private universities. All indicators of the two independent variables show a large correlation, which indicates that these two variables have an influence on the role of foundations in the level of authority for managing private universities.